PENERAPAN METODE BERMAIN PERAN UNTUK MENINGKATKAN KEMAMPUAN BERBICARA PADA MATA PELAJARAN BAHASA ARAB SISWA KELAS IX E MTSN 1 SERANG - Ellyza Amin (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2021)
Speaking is one of four language-learning aspects. Based on experience, this aspect is difficult to develop because students are afraid to speak. However, the researchers tried to solve the problem by applying different learning methods. The method chosen is role play. The researcher conducted action research by applying the role-play method to 32 IX E MTsN 1 Serang City students. The action research used the Kemmis-McTaggart model in two cycles. In the action research, the variables measured were the increase in students' speaking skills and opinions on applying the role-play method. The analysis results showed that the students' speaking ability increased from cycle I to cycle II, namely the average class result in the first cycle was 71.88%. In the second cycle, the class average was 88.28%, meaning an increase of 16.40%. Thus, the researcher concludes that the role-play method can help students improve speaking skills in Arabic subjects. In addition, students generally stated that they were happy with the use of the role-play method.